Information Sharing Model in Supporting Implementation of e-Procurement Service: Case of Bandung City - Gadang Ramantoko; Herry Irawan (International Journal of Supply Chain Management, 2017)
This research examines the factors influencing the Information Sharing Model in Supporting Implementation of e-Procurement Services: Case of Bandung City in its early maturity stage. The early maturity of information sharing stage was determined using e-Government Maturity Stage Conceptual Framework from Estevez. Bandung City e-Procurement Information Sharing system was categorized at stage 1 in Estevez model where the concern was mainly on assessing the benefit and risk of implementing the system. The Authors were using DeLone McLean (DM) Information System Success model to study benefit and risk of implementing the system in Bandung city. The model was then empirically tested by employing survey data that was collected from the available 40 listed supplier firms. DMs model adjusted by Klischewskis description was introducing Information Quality, System Quality, and Service Quality as independent variable; Usability and User Satisfaction as intermediate dependent variable; and Perceived Net Benefit as final dependent variable. The findings suggested that, all of the predictors in DMs model significantly influenced the net perceived benefit of implementing the e-Procurement system in the early maturity stage. The theoretical contribution of this research suggested that DMs model might find useful in modeling complex information technology successfulness such as the one used in e-Procurement service. This research could also have implications for policy makers (LPSE) and system providers (LKPP) following the introduction of the service. However, the small number of respondent might be considered limitation of the study. The model needs to be further tested using larger number of respondents by involving the population of the firms in extended boundary/municipality area around Bandung.